Evaluation of Physical Education Learning During the Covid 19 Pandemic in Elementary Schools in Gayamsari District, Semarang - Purnomo, Alip; Pramono, Harry; Hanani, Endang Sri (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Research background Several obstacles to studying PE during the COVID-19 pandemic must be resolved promptly. The research objectives : (1) analyse the antecedents of PE learning during the Covid-19 pandemic; (2) analyse PE learning transactions during the Covid-19 pandemic; and (3) analyse PE learning outcomes during the Covid-19 pandemic at Gayamsari District State Elementary Schools. Qualitative research, descriptive research design with evaluation of the Stake model: Antecedent, Transaction, and Outcomes. The data were collected from school principals, PE teachers, student guardians, and elementary students in the Gayamsari sub-district. Observation, interview, and documentation are all methods of data collection. Triangulation of sources and techniques is a technique for data validation. The data were qualitatively examined using the following steps: data collection, data reduction, data presentation, and conclusion drafting. The results of this study (1) Antencendent related to online PE learning planning was made by all teachers, including PE teachers. The implementation of PE learning during the COVID-19 pandemic is carried out online. (2) Transactions of online PE learning are carried out for only 1 hour of learning and the infrastructure used is the result of student modifications made at home (3) Outcomes of online PE learning in practice students become creative and independent in doing learning at home by making modification tools. The average student scores above the Minimum Completeness Criteria. The conclusion was that PE online learning was well-planned in terms of content and implementation. Continuous evaluations enable difficulties to be addressed and online PE learning to run successfully.